Method of immunohistochemical identification of extravillous cytotrophoblast in the structures of utero-placental bed and myometrium - Tiulienieva, Olena; Hoian, Anastasiia (Journal of Education, Health and Sport, 2021)
In this article, we discover and demonstrate the way of immunohistochemical identification of extravillous cytotrophoblast in the structures of the uteroplacental area and myometrium, which can be used to study the uteroplacental form of placental insufficiency, in the morphogenesis of which the key reason is a violation of the gestational changes of the spiral arteries of the uterus.